“LA GESTIÓN DEL TALENTO HUMANO EN LA EMPRESA HORMICONSTRUCCIONES CIA.LTDA DE LA CIUDAD DE LOJA - Maurad Jadàn, Jimmy Fabricio (2016)
This paper focuses on the management of human TALENT IN THE COMPANY HORMICONSTRUCCIONES CIA. LTDA. CITY OF LOJA management and administrative tools such as manuals, functions, welcome. The company HORMICONSTRUCCIONES CIA. LTDA. despite having appropriate infrastructure lacks adequate integration process and elementary tools to carry out the work in their jobs by their staff, and therefore can not improve their actions for the good of the herself and her personal development. as a starting point for the generation of an intervention proposal to strengthen the actions of staff activities and thus optimize the objectives set by the institution, for that reason and for the solution to this problem have considered the following: GENERAL OBJECTIVE: To establish methods and techniques on Human Resource Management in the company Hormiconstrucciones Cia. Ltda., Which will allow the best human element which significantly help the development of all company activities which specific objectives as follows:  To develop a suitable process for admission of employment (recruitment, selection, induction, integration, training, procurement) staff in Hormiconstrucciones Cia. Ltda.  Designing an organizational structure Hormiconstrucciones Cia. Ltda., (Structural organization, welcome manual and manual functions).  Conduct job evaluation points for the staff of the institution. 6 For it is then included as part of the work a manual function that allows them to meet each worker activities must meet a welcome manual that allows the person who will labor to know better shape the company for which it will labor and so assume the need to meet the objectives commitment; Likewise the integration process for staff entering to work in the company arises. Once the analysis and observation of Hormiconstrucciones Co. done. Ltda. And knowing the current situation of the company in the administrative and dedicated activity, we see that the company has been growing according to user requirements. Importantly describes the different methods and techniques that allowed carrying out work on the methodology used, the deductive method of the knowledge of general laws that apply to particular cases yielded information on the general problem of the integration process in Hormiconstrucciones Cia. Ltda .; and to identify the critical points on which they had to intervene to make this manual; the inductive method, which identified the most relevant aspects of the administration; Analytical method yielded information on the different aspects clearly running on the administration to propose appropriate corrective measures. Observation allowed to know precisely the processes that take place in the company among the techniques used; which allowed us to gather data and relate facts, highlighting characteristics in terms of their development, the interview served to obtain information related to the actions of staff and Co. Hormiconstrucciones activity. Ltda., Was made the manager of the company Mr. Oswaldo Eguiguren Hidalgo, to obtain all necessary information about services offered, areas that comprise the different jobs and staff working in it.; 7 and the survey yielded information on the actions of the employees of the company, was applied to staff working in it that are a total of 23 people. In the conclusions the most important aspects that affect the development of the inn is detailed; and whose base is achieved to raise the relevant solutions to finally raise the recommendations.